Vascular endothelial growth factor A inhibition remodels the transcriptional signature of lipid metabolism in psoriasis non‐lesional skin in 12 h ex vivo culture - Andrea Luengas‐Martinez; Dina Ismail; Ralf Paus; Helen S. Young (Wiley, 2024)
Abstract Background Vascular endothelial growth factor A (VEGF‐A)‐mediated angiogenesis is involved in the pathogenesis of psoriasis. VEGF‐A inhibitors are widely used to treat oncological and ophthalmological diseases but have not been used in psoriasis management. The molecular mechanisms underlying the effects of VEGF‐A inhibition in psoriatic skin remain unknown. Objectives To identify the genes and canonical pathways affected by VEGF‐A inhibition in non‐lesional and plaque skin ex vivo. Methods Total RNA sequencing was performed on skin biopsies from patients with psoriasis (n = 6; plaque and non‐lesional skin) and healthy controls (n = 6) incubated with anti‐VEGF‐A monoclonal antibody (bevacizumab, Avastin®) or human IgG1 isotype control for 12 h in serum‐free organ culture. Differentially expressed genes between paired control and treated samples with adjusted p‐values <0.1 were considered significant. Gene ontology and ingenuity pathway analysis was used to identify enriched biological processes, canonical pathways and upstream regulators. Results VEGF‐A inhibition upregulated the expression of genes involved in lipid metabolism. Pathway enrichment analysis identified the activation of pathways involved in fatty acids and lipid biosynthesis and degradation in non‐lesional skin and ferroptosis in plaque skin. VEGF‐A inhibition downregulated endothelial cell apoptosis in non‐lesional psoriasis skin and members of the interferon family were identified as potential regulators of the effects of VEGF‐A inhibition in non‐lesional skin. Conclusion Early response to VEGF‐A inhibition is associated with changes in lipid metabolism in non‐lesional psoriasis skin and cellular stress in psoriasis plaque. More investigation is needed to validate these findings.